SISTEM PAKAR PENYAKIT KUCING MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB - Miryam Petrus; Ilin Sukma; Gafrun Gafrun (Informatics Engineering Department of Halu Oleo University, 2019)
Cats are one of the animals that are popular among people of various backgrounds and ages. Often cat owners feel confused about the disease suffered by their pets so that they need the help of an expert who understands cat disease. So we need an application that can help in solving problems. The design of the system used is UML (Unified Modeling Language). While the method used in the application built is Forward Chaining using the Depth First Search algorithm. The expected outcome of this research is an application that can help the public know the disease as well as quick solutions and prevention to take action on pet cats. Keywords-Expert System, Depth First Search.